PENGGUNAAN MEDIA TANAM DAN PUPUK NPK TERHADAP HASIL RUMPUT TEKI (Cyperus rotundus) SERTA ANALISA KANDUNGAN KERIPIK OLAHANNYA - Wiwik Endah Rahayu; Atika Romalasari (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Nut grass is Cyperaceae group and underestimated its existence. Nut grass has many benefits so potential to be developed. This study aims to determine the effect of planting media and the addition of NPK fertilizer to the growth of the nut grass and find out the nutrient content of chips made from nut grass tuber. The design of this study was factorial complete randomized design (RAL) which consisted of two factors. First factor is Planting Media, consist of M1 = soil, M2 = Soil: Sand (2: 1), M3 = Soil: Compost Fertilizer (2: 1) and M4 = Soil: Cage Fertilizer (2: 1) and second factor is fertilizer dosage NPK 15: 15: 15 with the level P1 = Without NPK fertilizer, P2 = 5 g NPK fertilizer, P3 = 10 g NPK fertilizer. Research result showed that the media significantly affected the number of clumps, root weight, clump weight, overall weight and number of flowers but did not significantly affect the height, number of tubers and tuber weight. Fertilizer significantly affected the number of clumps, root weight, clump weight, overall weight, number of flowers, number of tubers and tuber weight but did not significantly affect the height at P≤0.05 level. Interaction between planting media and NPK fertilizer did not significantly affect all parameters. Keywords: Chips, NPK Fertilizer, Nut Grass, Planting Media